PENGUATAN BUDAYA NASIONAL DALAM SITUASI KRISIS BUDAYA - Sulardi, Sulardi (Jurnal Bestari, 2009)
<!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-no-proof:yes;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> There is something wrong in our education system. Our education do not give chance to appreciate and learn culture. Education on culture is done more on cognitive aspect; students are taught names both local and national cultures, folk dances, folk songs, and various traditions from many places in Indonesia without comprehending the real meaning of the culture itself. Furthermore, people are actually the culture legal owner. If this understanding is strong enough, claims on our cultures by another country will never happen. The most important is how to establish and teach people so that they have sense of belonging to their own cultures. So, it is time for central and local governments facilitate public?s participation in national culture affirmation.